Food Tourism: Traditional Food (‘Kuih-Muih’) Virtual Streaming - Mahdzar, Mazlina; Mohd Dzulkiflee, Nurul Izzati; Mohamed Yusoff3, Alisa; Mustapha, Nor Yuliana; Mohd Zulkifly, Nur Athirah; Zakaria, Mohamad Erwan (Multidisciplinary Applied Research and Innovation, 2021)
Food is the exploration of food as the purpose of tourism. It is considered a vital component of the tourism experience. As the Covid-19 got worse in Malaysia that limited movement of people to get through all countries. Streaming can be known as the activity of listening or watching video or audio directly from the internet. This traditional food virtual streaming focused on traditional “kuih-muih”. Tourist will be able to communicate and join our live sharing session about the local places. Besides, tourists can watch videos that are posted on the website for their references which also function as teaser videos providing infomations to the interesting attractions of Malaysia. The streaming can be watched directly on Youtube, Facebook, Instagram, or in other social media networks. This virtual streaming will show the unknown traditional food in all states of Malaysia. Traditional food streming included are such as Kelantan’s “Lompat Tikam”, “Jalur Emas”, Melaka “Kuih Gulung”, Sabah “Kuih Jala or Lampung”, “kuih cincin”,Terengganu “Tok Aji Serban” “kayu keramat”, Sarawak “ kuih cap” “kek lapis” and many more. With the use of social media the online community can recognize various “kuih-muih” easily using the prescribed methods of virtual streaming.